2014
DOI: 10.1002/2014jb010970
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the return times of great Himalayan earthquakes in eastern Nepal: Evidence from the Patu and Bardibas strands of the Main Frontal Thrust

Abstract: The return times of large Himalayan earthquakes are poorly constrained. Despite historical devastation of cities along the mountain range, definitive links between events and specific segments of the Main Frontal Thrust (MFT) are not established, and paleoseismological records have not documented the occurrence of several similar events at the same location. In east central Nepal, however, recently discovered primary surface ruptures of that megathrust in the A.D. 1255 and 1934 earthquakes are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
225
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(242 citation statements)
references
References 59 publications
17
225
0
Order By: Relevance
“…The M 7.8 earthquake was not completely unexpected in the Central Nepal region, as several studies had indicated the likelihood of earthquakes of magnitude greater than 8.0 based on the slip deficit estimation and accumulation of strain energy in the region. This has been anticipated in early 1990s and further confirmed by recent studies [2][3][4][5][6][7] . As shown in Figure 2, the major part of Nepal, including Kathmandu, lies in zone A on the seismic zoning map of Nepal 8,9 , whereas the districts of north Bihar adjoining the Nepal border lie in zones IV and V on the Indian seismic zone map 10 .…”
supporting
confidence: 74%
“…The M 7.8 earthquake was not completely unexpected in the Central Nepal region, as several studies had indicated the likelihood of earthquakes of magnitude greater than 8.0 based on the slip deficit estimation and accumulation of strain energy in the region. This has been anticipated in early 1990s and further confirmed by recent studies [2][3][4][5][6][7] . As shown in Figure 2, the major part of Nepal, including Kathmandu, lies in zone A on the seismic zoning map of Nepal 8,9 , whereas the districts of north Bihar adjoining the Nepal border lie in zones IV and V on the Indian seismic zone map 10 .…”
supporting
confidence: 74%
“…Paleoseismic data suggest that earthquakes in 1255 and 1934 ruptured to the surface along the MFT, south of Kathmandu (Bollinger et al, 2014). Field observations after the 2015 rupture, which nucleated on MHT (Avouac et al, 2015), suggest the rupture only extended to the base of the MFT.…”
Section: Fault Rupturementioning
confidence: 98%
“…The MCT is a series of thrusts separating the High Himalaya from the Lesser Himalaya (ibid.). Both the MBT and the MCT dip northward are no longer very active (Takada and Matsu'ura 2007); only the youngest, southernmost thrust (MFT) appears to be active in central Nepal (Bollinger et al 2014). Some studies have also suggested out-ofsequence thrusting, with possible thrust fault reactivation in the MCT zone (e.g., Hodges et al 2004;Seeber and Gornitz 1983).…”
Section: Tectonics and Setting Of Receiver Faultsmentioning
confidence: 99%